Tracking the stratosphere‐to‐surface impact of sudden stratospheric warmings - Hall, RJ; Mitchell, DM; Seviour, WJM; Wright, CJ (Journal of Geophysical Research: Atmospheres, 2020)
This is the final version. Available from Wiley via the DOI in this record. Data Availability Statement ERA-I and ERA40 data are freely available from the ECMWF website. ERA-I: https://www.ecmwf.int/ en/forecasts/datasets/reanalysis-datasets/era-interim. ERA40: https://apps.ecmwf.int/datasets/data/ era40-daily/levtype%3Dsfc. The NAO and AO indices are available from NOAA-CPC. NAO: https://www. cpc.ncep.noaa.gov/products/precip/CWlink/pna/nao.shtml. AO: https://www.cpc.ncep.noaa.gov/products/precip/CWlink/daily_ao_index/ao.shtml. Python code for the tracking algorithm is available from Zenodo (https://doi.org/10.5281/zenodo.4279027). Sudden stratospheric warming (SSW) events are extreme atmospheric regimes which can have a signature in surface weather up to 40 days after event onset in the stratosphere. SSWs can be classified as either vortex splitting or vortex displacement events, with the nature and timing of the surface impact potentially being different between the two. In this study, using ERA40/Interim reanalysis data, we develop a simple empirical downward tracking algorithm which for the first time allows us to estimate the time of surface impact for individual SSW events. We show that the surface impact following splitting events is, on average, about 1 week earlier than following displacement events, albeit with considerable variability. By compositing tropospheric responses around the identified date of surface impact, rather than around the central stratospheric onset date as common in previous studies, we can better constrain the surface signal of SSWs. We find that while the difference in North Atlantic Oscillation anomalies between split and displacement vortices is small, surface temperature anomalies over northwest Europe and northern Eurasia are significantly colder for splitting events, particularly over the UK just prior to the surface impact date. Displacement events on average are wetter over Northwest Europe around the time of surface impact, consistent with the jet stream being ...